Women’s Language in “The Nanny Diaries” Movie - Dharma Sanjaya, Ida Bagus Gede (Humanis; Vol 22 No 3 (2018), 2018)
This undergraduate thesis examine s the types of women’s linguistic feature found in the movie and script entitled “The Nanny Diaries” and analyze s the function of each type of women language features. This paper is inspired by the differentiation of the use of women and men language. It is known that women have their own way to choose their language. The main theory applied in this study is proposed by Lakoff (1973), who divided the linguistic features into two parts – lexical feature and syntactical feature. This theory is also used in analyzing the function of the features supported by the context of situation theory proposed by Halliday (1989). This study used an American comedy drama movie as data source. The movie is chosen as the data due to its richness in women’s linguistic features. The finding of the analysis showed that the women’s linguistic feature s found in the movie include the lexical feature (color-term, particles and evaluative adjective) and syntactical feature (tag-question, raising intonation in declarative and politeness in request and order). In general, the findng of the analysis of function of women’s linguistic feature is aimed to show politeness and avoid strong expression s .